Extreme turbulence control for wind turbines. Issue 5 (October 2017) - Kanev, Stoyan
The components of a wind turbine are designed to ensure that they can withstand the (fatigue and extreme) loads during their lifetime. To this end, the loads are analyzed using simulations under a large set of design conditions. One of the most demanding design condition, however, is operation under extreme turbulence conditions. For many turbines, this is a design-driving load case, as is the case with the InnWind 10-MW reference wind turbine. To present, reduction of loads during extreme turbulence using the wind turbine controller has not been considered explicitly. In this report, an extreme turbulence control algorithm is developed to actively reduce the ultimate loads on the main turbine components during operation in extreme turbulence conditions. The benefits of the algorithm are demonstrated in two test cases: with the InnWind 10-MW and InnWind 20-MW reference wind turbines.